Devices for protecting bridge superstructure from pounding and unseating damages: an overview - Shrestha, Bipin; Hao, Hong; Bi, Kaiming (Taylor & Francis, 2017)
Previous earthquakes have highlighted the seismic vulnerability of bridges due to excessive movements at expansion joints. This movement could lead to the catastrophic unseating failure if the provided seat width is inadequate. Moreover, seismic pounding is inevitable during a strong earthquake due to the limited gap size normally provided at the expansion joints. Various types of restrainers, dampers and other devices have been proposed to limit the joint movement or to accommodate the joint movement so that the damages caused by excessive relative displacements could be mitigated. To select and design appropriate devices to mitigate the relative displacement-induced damages to bridge structures during earthquake shaking, it is important that results from the previous studies are well understood. This paper presents an overview on various pounding and unseating mitigation devices that have been proposed by various researchers. Based on an extensive review of up-to-date literatures, the merits and limitations of these devices are discussed.